LOGISTIC CART - Ruskulis, Mārtiņš; Kucins, Emīls; Martinovs, Andris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Project of the logistic cart allows the number of companies to develop the efficiency and productivity of their work following the tendencies and development of the global technologies. Using such logistic carts in industrial warehouses and in distributions centres enable entrepreneurs to save money and other resources that they otherwise need to spend on many employees that do their work manually. Such logistic carts would be beneficial for producers and shops that have a great variety of products and raw materials in warehouses. Such product in Europe has great attention and has good sales but in Latvia we don’t have any companies that produce logistic carts so the geographical position of the country allows to expand the markets in Russia and other Baltic countries, as logistic carts there are not widely used and produced.